2004
DOI: 10.1074/jbc.m401337200
|View full text |Cite
|
Sign up to set email alerts
|

The Second Intracellular Loop of the Glycine Transporter 2 Contains Crucial Residues for Glycine Transport and Phorbol Ester-induced Regulation

Abstract: Na ؉ and Cl ؊ -coupled glycine transporters control the availability of glycine neurotransmitter in the synaptic cleft of inhibitory glycinergic pathways. In this report, we have investigated the involvement of the second intracellular loop of the neuronal glycine transporter 2 (GLYT2) on the protein conformational equilibrium and the regulation by 4␣-phorbol 12 myristate 13-acetate (PMA). By substituting several charged (Lys-415, Lys-418, and Lys-422) and polar (Thr-419 and Ser-420) residues for different ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
53
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 48 publications
1
53
0
Order By: Relevance
“…Regulation of the transport activity by protein kinase G has been reported to be controlled by homologous serine residues present in the N-terminal portion of the fifth transmembrane domain (64,65), a cytoplasmic protein region located within or near by the permeation pathway of these 12 transmembrane domain proteins (63). The homologous serine residue in GLYT2 is Ser-420, which lies close to a protein kinase C regulatory region (7). In a previous work, we generated mutant S420A in GLYT2 and showed that it has similar properties than wild type, although the replacement by Glu produced a PKCresistant transporter (7).…”
Section: Effect Of P2y Receptor Activation On Glycine Transport By Glmentioning
confidence: 99%
See 3 more Smart Citations
“…Regulation of the transport activity by protein kinase G has been reported to be controlled by homologous serine residues present in the N-terminal portion of the fifth transmembrane domain (64,65), a cytoplasmic protein region located within or near by the permeation pathway of these 12 transmembrane domain proteins (63). The homologous serine residue in GLYT2 is Ser-420, which lies close to a protein kinase C regulatory region (7). In a previous work, we generated mutant S420A in GLYT2 and showed that it has similar properties than wild type, although the replacement by Glu produced a PKCresistant transporter (7).…”
Section: Effect Of P2y Receptor Activation On Glycine Transport By Glmentioning
confidence: 99%
“…The homologous serine residue in GLYT2 is Ser-420, which lies close to a protein kinase C regulatory region (7). In a previous work, we generated mutant S420A in GLYT2 and showed that it has similar properties than wild type, although the replacement by Glu produced a PKCresistant transporter (7). To test the ability of the homologous serine residues in the GLYT modulation by P2Y 1 R, we constructed the homologous mutant in GLYT1 (S244A) and characterized the transport activity of the mutants expressed in COS7 cells (Fig.…”
Section: Effect Of P2y Receptor Activation On Glycine Transport By Glmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, amino-terminal phosphorylation has been shown to be important for reversed dopamine transport by DAT (23). In contrast, PKC-dependent phosphorylation of the second intracellular loop of glycine transporter 1 has been implicated in the phorbol estermediated down-regulation of this transporter (24), thus illustrating differences in the regulation of endocytosis of different members of this transporter family (25).…”
mentioning
confidence: 99%